Stillness in the Composition Classroom: Insight, Incubation, Improvisation, Flow, and Meditation - Ryan Crawford; Andreas Willhoff (Journal of the Assembly for Expanded Perspectives on Learning, 2013)
Studies of brain images provide scientific justification for encouraging meditation among young writers.